1990
DOI: 10.1159/000125562
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Release of Luteinizing Hormone and Gonadotropin-Releasing Hormone in Ovariectomized Rats

Abstract: The effect of aging on the release of gonadotropin-releasing hormone (GnRH) in vitro and of luteinizing hormone (LH) both in vivo and in vitro in ovariectomized (Ovx) rats was studied. Old (21–24 months) and young (3–4 months) rats were Ovx before use. They were injected subcutaneously with estradiol benzoate (25 µg/kg) or sesame oil for 3 days and then challenged with GnRH (0.5,2 or 10 µg/kg) via a jugular catheter. Blood samples were collected immediately before and at 5, 10, 20, 40 and 60 min following GnRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…The second possibility was suggested earlier [26, 27, 28, 29, 30], and the present results support it, but the first one was also quite probable. There have been several demonstrations that aging decreases the transmitter release in response to K + depolarization or electrical stimulation in the CNS neurons.…”
Section: Discussionsupporting
confidence: 88%
“…The second possibility was suggested earlier [26, 27, 28, 29, 30], and the present results support it, but the first one was also quite probable. There have been several demonstrations that aging decreases the transmitter release in response to K + depolarization or electrical stimulation in the CNS neurons.…”
Section: Discussionsupporting
confidence: 88%
“…In intact (proestrous), OVX, or OVX plus estradiol-treated female rats (the latter during the LH surge), Rubin (1992) reported that basal GnRH release is higher from isolated hypothalami of middle-aged than young rats, although potassium-stimulated GnRH release is equivalent between the two ages. A different result was reported by Hwang et al (1990), who demonstrated that basal GnRH release from explants of young (, 4 months) and old (21 -24 months) OVX rats is comparable, whereas potassium-stimulated GnRH release is greater in the young rats. Differences between these two reports may be due to differences in ages of animals, as the Hwang study used much older rats than the Rubin study.…”
Section: In Vitro Release Of Gnrhcontrasting
confidence: 56%
“…It has been well documented for the reproductive axis that the hypothalamus of aged animals has a blunted response to estrogen deprivation or replacement compared with young animals (45)(46)(47)(48)(49)(50)(51)(52). This may be caused, at least in part, by the condition of constant estrous or diestrous, because both conditions involve constant levels of unopposed estrogen rather than the normal fluctuations of estradiol and progesterone in the ovarian cycle (53)(54)(55), and this condition in the aged animal may underlie the blunted spine response we observed.…”
Section: Discussionmentioning
confidence: 99%